DETERMINANTS OF UNINTENDED PREGNANCY AMONG MARRIED WOMEN AGED 15-49 YEARS IN EAST JAVA - Indah Lutfiya; Mursyidul Ibad; Afif Kurniawan; Nuke Amalia; Diyah Herowati (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2022)
The percentage of Unintended Pregnancy or Kehamilan Tidak Diinginkan (KTD) in Indonesia is still 17.5%. East Java contributed for 14.6% of cases of KTD during 2019. The increase in fertility rates and maternal mortality cases in Indonesia is partly due to KTD. This study will analyze the determinants of the incident of KTD in women of childbearing age or Wanita Usia Subur (WUS) in East Java. This study is a non-reactional study with a Cross-sectional design using data on the Program Performance and Accountability Survey (PPAS) for Family Planning and Family Development Program (KKBPK) 2019. Sample in this study were 2,650 married WUS with ages 15-49 years. Secondary data were analyzed using multiple logistic regression tests. Some factors that determine the incidence of unintended pregnancy include mother's age (p=0.000), age of first marriage or Usia Kawin Pertama (UKP) (p=0.004), number of living children (p=0.000), welfare level (p=0.004), residence (p=0.043), knowledge of contraception (p=0.022), history of contraceptive use (p=0.001), access of information (p=0.000), and family planning decisions (p=0.003). Meanwhile mother's education (p=0.998), mother's occupation (p=0.362), and insurance ownership (p=0,750) did not affect the case of KTD in East Java. New policies and innovations that are more targeted are needed so that prospective acceptors receive contraceptive services easily and affordably so as to reduce the number of KTD. Optimizing the role of the Family   Planning   Field Officer or Petugas Lapangan   Keluarga   Berencana (PLKB) to increase the rate of the use of modern contraceptives in East Java.